Adverse events related to central venous catheters (CVC) and the influence of CVC characteristics on peripheral blood hematopoietic progenitor cell collection in children - Zubicaray, Josune; Martin-Consuegra, Sofía; Nieto, Monserrat; Albi, Gustavo; Iriondo, June; Sebastian, Elena; Gálvez, Eva; Molina, Blanca; González-Vicent, Marta; de Pablo, Jesus Gonzalez; Castillo, Ana; Ramírez, Manuel; et al. (Frontiers in Pediatrics, 2023)
Introduction: The use of peripheral blood progenitor cells (PBPCs) as a source for hematopoietic stem cell transplantation (HSCT) in pediatric healthy donors is still under debate. The risk of a central venous catheter (CVC) placement and catheter-related complications continue to be the main arguments to discourage its use. Methods: we present a retrospective analysis of 140 PBPC collections in pediatric patients and donors, describing adverse events (AE) related to CVCs as well as the influence of catheterrelated variables on the efficiency of the leukapheresis. Results: 14 CVC-related AEs were recorded (10%). The most common was fever in 5 patients, 4 of which had a catheter-related bacteriemia. Thrombotic events were only observed in 3 patients with active malignancy. A healthy donor presented a moderate bleeding after catheter withdrawal that resolved with local measures, and none of the rest presented any AE. Regarding variables related to the development of AEs, the subject group (patient or donor) was the only one significantly associated (p<0.0001). Of interest, efficiency was also related to catheter location, being worse in those located in the femoral vein than in into the jugular or the subclavian veins (p<0.05). In a multivariate analysis, the only variable significantly associated was catheter size (beta 0.238, p<0.01). Discussion: Placing a CVC for PBPC collection in pediatric subjects is overall safe; CVC-related complications in pediatric healthy donors are very rare. Furthermore, we should try to place catheters of the largest caliber possible, since the efficiency of the collection is related to this variable.